Polarizing plate with retardation layer and pressure-sensitive adhesive layer, and image display device using the retardation layer and pressure-sensitive adhesive layer
Patent Information
- Application Number
- JP2022508125
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2020-03-18
- Filing Date
- 2021-02-08
- Publication Date
- 2025-03-11
- Estimated Expiration
- 2041-02-08
AI Technical Summary
【0006】 本発明の実施形態によれば、偏光子と位相差層との間の粘着剤層の糊ずれ量ならびに位相差層の遅相軸方向の加熱収縮率を組み合わせて最適化することにより、高温環境下において位相差ムラが抑制された位相差層および粘着剤層付偏光板を実現することができる。その結果、高温環境下において色ムラが抑制された画像表示装置を実現することができる。
Smart Images

Figure 0007644090000009 
Figure 0007644090000001 
Figure 0007644090000002
Abstract
Description
[Technical field]
[0001] The present invention relates to a retardation layer and a polarizing plate attached with a pressure-sensitive adhesive layer, and an image display device using the retardation layer and the polarizing plate attached with a pressure-sensitive adhesive layer. [Background technology]
[0002] In recent years, image display devices, such as liquid crystal display devices and electroluminescence (EL) display devices (e.g., organic EL display devices, inorganic EL display devices), have rapidly become widespread. A polarizing plate and a retardation plate are typically used in image display devices. In practice, a retardation layer-attached polarizing plate in which a polarizing plate and a retardation plate are integrated is widely used (e.g., Patent Document 1). However, retardation unevenness occurs in polarizing plates with retardation layers in high-temperature environments, and as a result, color unevenness may occur in image display devices in high-temperature environments. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] Patent No. 3325560 Summary of the Invention [Problem to be solved by the invention]
[0004] The present invention has been made to solve the above-mentioned problems of the conventional art, and its main object is to provide a retardation layer and a polarizing plate with a pressure-sensitive adhesive layer that can realize an image display device in which retardation unevenness is suppressed in a high-temperature environment and color unevenness is suppressed in a high-temperature environment. [Means for solving the problem]
[0005] The retardation layer and the polarizing plate with an adhesive layer according to an embodiment of the present invention include a polarizing plate including a polarizer, a retardation layer bonded to the polarizing plate via a first adhesive layer, and a second adhesive layer provided as an outermost layer on the side opposite to the polarizing plate of the retardation layer. The retardation layer is composed of a stretched film of a resin film, satisfies the relationship of Re(450) < Re(550), and has a shrinkage rate in the slow axis direction of 4% or less when heated at 80°C to 125°C for up to 180 minutes. The amount of adhesive displacement after the heating test of the first adhesive layer at 85°C for 500 hours is 300 μm or more. Here, Re(450) and Re(550) are the in-plane retardations measured with light of wavelengths 450 nm and 550 nm at 23°C, respectively. In one embodiment, Re(550) of the retardation layer is 100 nm to 200 nm, and the angle formed by the slow axis of the retardation layer and the absorption axis of the polarizer is 40° to 50° or 130° to 140°. In one embodiment, the thickness of the retardation layer is 15 μm to 60 μm. In one embodiment, the stretched film constituting the retardation layer has been subjected to a heat treatment of heating at a temperature of 105°C or higher for 2 minutes or more. In one embodiment, the retardation layer and the polarizing plate with an adhesive layer further have another retardation layer having a refractive index characteristic showing a relationship of nz > nx = ny between the retardation layer and the second adhesive layer. In one embodiment, the retardation layer includes at least one bonding group selected from the group consisting of a carbonate bond and an ester bond, and at least one structural unit selected from the group consisting of a structural unit represented by the following general formula (1) and a structural unit represented by the following general formula (2), and a resin having positive refractive index anisotropy; an acrylic resin; and the content of the acrylic resin is 0.5% by mass to 2.0% by mass, the acrylic resin contains 70% by mass or more of a structural unit derived from methyl methacrylate, and its weight average molecular weight Mw is 10,000 to 200,000:
Chemical formula
Chemical formula
[0006] According to the embodiment of the present invention, by optimizing the combination of the adhesive slippage amount of the adhesive layer between the polarizer and the retardation layer and the heat shrinkage rate in the slow axis direction of the retardation layer, it is possible to realize a retardation layer and a polarizing plate with an adhesive layer in which retardation unevenness is suppressed in a high-temperature environment. As a result, it is possible to realize an image display device in which color unevenness is suppressed in a high-temperature environment. [Brief description of the drawings]
[0007] [Figure 1] FIG. 1 is a schematic cross-sectional view of a retardation layer- and pressure-sensitive adhesive layer-attached polarizing plate according to one embodiment of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0008] Representative embodiments of the present invention will be described below, but the present invention is not limited to these embodiments.
[0009] (Definition of terms and symbols) The definitions of terms and symbols used in this specification are as follows. (1) Refractive index (nx, ny, nz) "nx" is the refractive index in the direction in which the in-plane refractive index is maximum (i.e., the slow axis direction), "ny" is the refractive index in the direction perpendicular to the slow axis in the plane (i.e., the fast axis direction), and "nz" is the refractive index in the thickness direction. (2) In-plane phase difference (Re) "Re(λ)" is the in-plane retardation of a film measured with light of wavelength λ nm at 23° C. For example, "Re(450)" is the in-plane retardation of a film measured with light of wavelength 450 nm at 23° C. Re(λ) is calculated by the formula: Re=(nx-ny)×d, where d(nm) is the thickness of the film. (3) Retardation in the thickness direction (Rth) "Rth(λ)" is the retardation in the thickness direction of a film measured with light of wavelength λ nm at 23° C. For example, "Rth(450)" is the retardation in the thickness direction of a film measured with light of wavelength 450 nm at 23° C. Rth(λ) is calculated by the formula: Rth=(nx-nz)×d, where d(nm) is the thickness of the film. (4) Nz coefficient The Nz coefficient is calculated by Nz=Rth / Re. (5)Angle When angles are referred to herein, unless otherwise specified, the angles include angles in both clockwise and counterclockwise directions.
[0010] A. Overall configuration of polarizing plate with retardation layer and adhesive layer Figure 1 is a schematic cross-sectional view of a retardation layer and a polarizing plate with an adhesive layer according to one embodiment of the present invention. The retardation layer and polarizing plate with adhesive layer 100 in the illustrated example includes a polarizing plate 10, a retardation layer 30 bonded to the polarizing plate 10 via a first adhesive layer 20, and a second adhesive layer 40 provided as the outermost layer on the side of the retardation layer 30 opposite to the polarizing plate 10. The second adhesive layer 40 enables the retardation layer and polarizing plate with adhesive layer to be attached to an image display cell. The polarizing plate 10 includes a polarizer 11, a first protective layer 12 disposed on one side of the polarizer 11, and a second protective layer 13 disposed on the other side of the polarizer 11. Depending on the purpose, one of the first protective layer 12 and the second protective layer 13 may be omitted. For example, since the retardation layer 30 can also function as a protective layer for the polarizer 11, the second protective layer 13 may be omitted. The angle formed between the slow axis of the retardation layer 30 and the absorption axis of the polarizer 11 is preferably 40° to 50°, more preferably 42° to 48°, still more preferably 44° to 46°, and particularly preferably about 45°; or preferably 130° to 140°, more preferably 132° to 138°, still more preferably 134° to 136°, and particularly preferably about 135°.
[0011] The retardation layer 30 is composed of a stretched film of a resin film, satisfies the relationship Re(450) < Re(550), and has a shrinkage rate in the slow axis direction of 4% or less when heated at 80°C to 125°C for up to 180 minutes. The Re(550) of the retardation layer 30 is typically 100 nm to 200 nm. The amount of adhesive displacement after a heating test of the first adhesive layer 20 at 85°C for 500 hours is 300 μm or more. Details of each layer constituting the retardation layer and polarizing plate with adhesive layer will be described later.
[0012] In one embodiment, the retardation layer and polarizing plate with adhesive layer may further have another retardation layer (not shown) between the retardation layer 30 and the second adhesive layer 40. The another retardation layer typically exhibits a refractive index characteristic of nz > nx = ny. By providing such another retardation layer, reflection in an oblique direction can be preferably prevented, and a wide viewing angle of the antireflection function can be achieved.
[0013] In one embodiment, the retardation layer and the adhesive layer-attached polarizing plate may further have a conductive layer or an isotropic substrate with a conductive layer (not shown). When the conductive layer or the isotropic substrate with a conductive layer is provided, the retardation layer and the adhesive layer-attached polarizing plate may be applied to a so-called inner touch panel type input display device in which a touch sensor is incorporated between an image display cell (e.g., an organic EL cell) and a polarizing plate. The conductive layer or the isotropic substrate with a conductive layer is typically provided between the retardation layer 30 and the second adhesive layer 40. When another retardation layer is provided, the other retardation layer and the conductive layer or the isotropic substrate with a conductive layer are typically provided in this order from the retardation layer 30 side.
[0014] The retardation layer and the pressure-sensitive adhesive layer-attached polarizing plate may have an additional retardation layer (not shown). The additional retardation layer may be provided in combination with another retardation layer, or may be provided alone (i.e., without providing another retardation layer). The optical properties (e.g., refractive index properties, in-plane retardation, Nz coefficient, photoelastic coefficient), thickness, arrangement position, etc. of the additional retardation layer may be appropriately set according to the purpose.
[0015] The retardation layer and the adhesive layer-attached polarizing plate may be in the form of a sheet or in the form of a long sheet. In this specification, the term "long sheet" means a long and narrow shape whose length is sufficiently long relative to its width, and includes, for example, a long and narrow shape whose length is 10 times or more, preferably 20 times or more, relative to its width. The long retardation layer and the adhesive layer-attached polarizing plate can be wound into a roll.
[0016] For practical purposes, it is preferable that a release film is temporarily attached to the surface of the second pressure-sensitive adhesive layer 40 until the retardation layer and the pressure-sensitive adhesive layer-attached polarizing plate are used. By temporarily attaching the release film, the second pressure-sensitive adhesive layer is protected and the retardation layer and the pressure-sensitive adhesive layer-attached polarizing plate can be formed into a roll.
[0017] Hereinafter, components of the retardation layer and the pressure-sensitive adhesive layer-attached polarizing plate will be described.
[0018] B. Polarizer Any appropriate polarizer can be adopted as the polarizer 11. For example, the resin film forming the polarizer may be a single-layer resin film or a laminate of two or more layers.
[0019] Specific examples of polarizers made of a single-layer resin film include hydrophilic polymer films such as polyvinyl alcohol (PVA) films, partially formalized PVA films, and partially saponified ethylene-vinyl acetate copolymer films that have been dyed with iodine or a dichroic substance such as a dichroic dye and stretched, and polyene-based oriented films such as dehydrated PVA films and dehydrochlorinated polyvinyl chloride films. A polarizer obtained by dyeing a PVA film with iodine and uniaxially stretching it is preferably used because of its excellent optical properties.
[0020] The dyeing with iodine is carried out, for example, by immersing the PVA-based film in an aqueous iodine solution. The stretching ratio of the uniaxial stretching is preferably 3 to 7 times. The stretching may be carried out after the dyeing treatment, or may be carried out while dyeing. Alternatively, the film may be stretched and then dyed. If necessary, the PVA-based film may be subjected to a swelling treatment, a crosslinking treatment, a washing treatment, a drying treatment, or the like. For example, by immersing the PVA-based film in water and washing it with water before dyeing, it is possible to wash off dirt and antiblocking agents on the surface of the PVA-based film, and also to swell the PVA-based film and prevent uneven dyeing.
[0021] Specific examples of polarizers obtained using laminates include a laminate of a resin substrate and a PVA-based resin layer (PVA-based resin film) laminated on the resin substrate, or a polarizer obtained using a laminate of a resin substrate and a PVA-based resin layer coated on the resin substrate. A polarizer obtained using a laminate of a resin substrate and a PVA-based resin layer coated on the resin substrate can be produced by, for example, applying a PVA-based resin solution to the resin substrate and drying the resin substrate to form a PVA-based resin layer on the resin substrate to obtain a laminate of the resin substrate and the PVA-based resin layer; stretching and dyeing the laminate to make the PVA-based resin layer a polarizer. In this embodiment, stretching typically includes immersing the laminate in an aqueous solution of boric acid to stretch it. Furthermore, stretching may further include, as necessary, stretching the laminate in air at a high temperature (for example, 95°C or higher) before stretching in the aqueous solution of boric acid. The obtained laminate of resin substrate / polarizer may be used as it is (i.e., the resin substrate may be used as a protective layer for the polarizer), or the resin substrate may be peeled off from the laminate of resin substrate / polarizer, and any suitable protective layer may be laminated on the peeled surface depending on the purpose. Details of the method for producing such a polarizer are described in, for example, JP2012-73580A and JP6470455A. The descriptions in these patent documents are incorporated herein by reference.
[0022] The polarizer may preferably be composed of a single-layer resin film. With such a configuration, a retardation layer and a polarizing plate with a pressure-sensitive adhesive layer, in which retardation unevenness in a high-temperature environment is suppressed, can be obtained due to a synergistic effect with the optimization of the first pressure-sensitive adhesive layer and the second pressure-sensitive adhesive layer.
[0023] The thickness of the polarizer is preferably 15 μm or less, more preferably 1 μm to 12 μm, and further preferably 3 μm to 12 μm. When the thickness of the polarizer is within this range, curling during heating can be well suppressed, and good appearance durability during heating can be obtained.
[0024] The polarizer preferably exhibits absorption dichroism at any wavelength of 380 nm to 780 nm. The single transmittance of the polarizer is, for example, 41.5% to 46.0%, preferably 43.0% to 46.0%, and more preferably 44.5% to 46.0%. The degree of polarization of the polarizer is preferably 97.0% or more, more preferably 99.0% or more, and even more preferably 99.9% or more.
[0025] C. Protective layer The first protective layer 12 and the second protective layer 13 are each formed of any suitable film that can be used as a protective layer for a polarizer. Specific examples of materials that are the main components of the film include cellulose-based resins such as triacetyl cellulose (TAC), and transparent resins such as polyesters, polyvinyl alcohols, polycarbonates, polyamides, polyimides, polyethersulfones, polysulfones, polystyrenes, polynorbornenes, polyolefins, (meth)acrylics, and acetates. Other examples include thermosetting resins or ultraviolet-curing resins such as (meth)acrylics, urethanes, (meth)acrylic urethanes, epoxys, and silicones. Other examples include glassy polymers such as siloxane polymers. Polymer films described in JP 2001-343529 A (WO01 / 37007) can also be used. The material for this film may be, for example, a resin composition containing a thermoplastic resin having a substituted or unsubstituted imide group in the side chain, and a thermoplastic resin having a substituted or unsubstituted phenyl group and a nitrile group in the side chain, such as a resin composition containing an alternating copolymer of isobutene and N-methylmaleimide, and an acrylonitrile-styrene copolymer. The polymer film may be, for example, an extrusion molded product of the above resin composition.
[0026] The retardation layer and the polarizing plate with adhesive layer are typically arranged on the viewing side of the image display device, as described later, and the first protective layer 12 is typically arranged on the viewing side. Therefore, the first protective layer 12 may be subjected to surface treatment such as hard coat treatment, anti-reflection treatment, anti-sticking treatment, and anti-glare treatment, as necessary. In addition, the first protective layer 12 may be subjected to treatment for improving visibility when viewed through polarized sunglasses (typically, imparting an (elliptical) polarizing function, imparting an ultra-high phase difference) as necessary. By performing such treatment, excellent visibility can be achieved even when the display screen is viewed through polarized lenses such as polarized sunglasses. Therefore, the retardation layer and the polarizing plate with adhesive layer can be suitably applied to image display devices that can be used outdoors.
[0027] The thickness of the first protective layer is typically 300 μm or less, preferably 100 μm or less, more preferably 5 μm to 80 μm, and further preferably 10 μm to 60 μm. When a surface treatment is applied, the thickness of the outer protective layer includes the thickness of the surface treatment layer.
[0028] In one embodiment, the second protective layer 13 is preferably optically isotropic. In this specification, "optically isotropic" means that the in-plane retardation Re(550) is 0 nm to 10 nm, and the retardation Rth(550) in the thickness direction is -10 nm to +10 nm.
[0029] C. Retardation layer C-1. Characteristics of the retardation layer As described above, the in-plane retardation Re(550) of the retardation layer is 100 nm to 200 nm, preferably 110 nm to 180 nm, more preferably 120 nm to 160 nm, and further preferably 130 nm to 150 nm. That is, the retardation layer can function as a so-called λ / 4 plate.
[0030] The retardation layer satisfies the relationship of Re(450) < Re(550) as described above, and preferably further satisfies the relationship of Re(550) < Re(650). That is, the retardation layer exhibits an inverse-dispersion wavelength dependence in which the retardation value increases according to the wavelength of the measurement light. Re(450) / Re(550) of the retardation film is, for example, greater than 0.5 and less than 1.0, preferably 0.7 to 0.95, more preferably 0.75 to 0.92, and even more preferably 0.8 to 0.9. Re(650) / Re(550) is preferably 1.0 or more and less than 1.15, more preferably 1.03 to 1.1.
[0031] Since the retardation layer has an in-plane retardation as described above, it has a relationship of nx > ny. As long as the retardation layer has a relationship of nx > ny, it exhibits any appropriate refractive index characteristics. The refractive index characteristics of the retardation layer typically exhibit a relationship of nx > ny ≥ nz. Here, "ny = nz" includes not only the case where ny and nz are exactly equal but also the case where they are substantially equal. Therefore, within a range that does not impair the effects of the present invention, ny < nz may occur. The Nz coefficient of the retardation layer is preferably 0.9 to 2.0, more preferably 0.9 to 1.5, and even more preferably 0.9 to 1.2. By satisfying such a relationship, when the retardation layer and the polarizing plate with an adhesive layer are used in an image display device, a very excellent reflected hue can be achieved.
[0032] The thickness of the retardation layer can be set so as to function most appropriately as a λ / 4 plate. In other words, the thickness can be set so as to obtain a desired in-plane retardation. Specifically, the thickness is preferably 15 μm to 60 μm, more preferably 20 μm to 55 μm, and most preferably 20 μm to 45 μm. In an embodiment of the present invention, the thickness of the retardation layer can be made significantly thinner than that of a λ / 4 plate composed of a normal resin film.
[0033] In the embodiment of the present invention, the retardation layer has a shrinkage rate in the slow axis direction of 4% or less, preferably 3.5% or less, and more preferably 3% or less, when heated for 180 minutes at 80° C. to 125° C. As described above, the shrinkage rate is preferably as small as possible, and the lower limit thereof may be, for example, 0.5%.
[0034] The breaking elongation of the stretched film constituting the retardation layer is preferably 200% or more, more preferably 210% or more, even more preferably 220% or more, and particularly preferably 245% or more. The upper limit of the breaking elongation may be, for example, 500%. The stretched film used in the retardation layer in the embodiment of the present invention is excellent in retardation expression and also has excellent extensibility, so that the desired in-plane retardation can be realized with a very thin thickness due to the synergistic effect of these. In this specification, the "breaking elongation" means the elongation rate when the film breaks in fixed-end uniaxial stretching at a predetermined stretching temperature (for example, Tg-2°C).
[0035] The retardation layer preferably has an absolute value of the photoelastic coefficient of 20×10 -12 (m 2 / N) or less, more preferably 1.0×10 -12 (m 2 / N)~15×10 -12 (m 2 / N), and more preferably 2.0×10 -12 (m 2 / N)~12×10 -12 (m 2 When the absolute value of the photoelastic coefficient is within such a range, display unevenness can be suppressed when the retardation layer and the pressure-sensitive adhesive layer-attached polarizing plate are applied to an image display device.
[0036] C-2. Materials for the retardation layer The retardation layer typically contains a resin containing at least one bond group selected from the group consisting of carbonate bonds and ester bonds. In other words, the retardation layer contains a polycarbonate-based resin, a polyester-based resin, or a polyestercarbonate-based resin (hereinafter, these may be collectively referred to as polycarbonate-based resins, etc.). The polycarbonate-based resins, etc. contain at least one structural unit selected from the group consisting of the structural unit represented by the above general formula (1) and / or the structural unit represented by the above general formula (2). These structural units are structural units derived from divalent oligofluorene, and may be hereinafter referred to as oligofluorene structural units. Such polycarbonate-based resins, etc. have positive refractive index anisotropy.
[0037] The retardation layer typically further contains an acrylic resin. The content of the acrylic resin is 0.5% by mass to 1.5% by mass. In this specification, the percentage or part in "mass" is synonymous with the percentage or part in "weight".
[0038] C-2-1. Polycarbonate resins, etc. <Oligofluorene structural unit> The oligofluorene structural unit is represented by the above general formula (1) or (2). In general formulas (1) and (2), R 1 ~R 3 are each independently a direct bond or a substituted or unsubstituted alkylene group having 1 to 4 carbon atoms; R 4 ~R 9 are each independently a hydrogen atom, a substituted or unsubstituted alkyl group having 1 to 10 carbon atoms, a substituted or unsubstituted aryl group having 4 to 10 carbon atoms, a substituted or unsubstituted acyl group having 1 to 10 carbon atoms, a substituted or unsubstituted alkoxy group having 1 to 10 carbon atoms, a substituted or unsubstituted aryloxy group having 1 to 10 carbon atoms, a substituted or unsubstituted amino group, a substituted or unsubstituted vinyl group having 1 to 10 carbon atoms, a substituted or unsubstituted ethynyl group having 1 to 10 carbon atoms, a sulfur atom having a substituent, a silicon atom having a substituent, a halogen atom, a nitro group, or a cyano group. 4 ~R 9may be the same or different, R 4 ~R 9 At least two adjacent groups among these may be bonded to each other to form a ring.
[0039] The content of the oligofluorene structural unit in the polycarbonate resin or the like is preferably 1% by mass to 40% by mass, more preferably 10% by mass to 35% by mass, further preferably 15% by mass to 30% by mass, and particularly preferably 18% by mass to 25% by mass, based on the entire resin. If the content of the oligofluorene structural unit is too high, problems such as too high photoelastic coefficient, insufficient reliability, and insufficient retardation expression may occur. Furthermore, since the proportion of the oligofluorene structural unit in the resin increases, the range of molecular design becomes narrow, and when modification of the resin is required, improvement may be difficult. On the other hand, even if the desired reverse dispersion wavelength dependency is obtained with a very small amount of the oligofluorene structural unit, in this case, the optical properties change sensitively according to a slight variation in the content of the oligofluorene structural unit, so that it may be difficult to manufacture so that the various properties fall within a certain range.
[0040] Details of the oligofluorene structural unit are described, for example, in International Publication No. WO 2015 / 159928, the disclosure of which is incorporated herein by reference.
[0041] <Other structural units> Polycarbonate resins and the like can typically contain other structural units in addition to oligofluorene structural units. In one embodiment, the other structural units can be preferably derived from dihydroxy compounds or diester compounds. In order to achieve the desired reverse dispersion wavelength property, it is necessary to incorporate a structural unit having positive intrinsic birefringence into the polymer structure together with the oligofluorene structural unit having negative intrinsic birefringence, so that the other monomers to be copolymerized are more preferably dihydroxy compounds or diester compounds that are the raw materials of structural units having positive birefringence.
[0042] Examples of the copolymerizable monomer include compounds capable of introducing a structural unit containing an aromatic ring, and compounds not capable of introducing a structural unit containing an aromatic ring, that is, compounds constituted by an aliphatic structure. Specific examples of the compound having an aliphatic structure are as follows: dihydroxy compounds of linear aliphatic hydrocarbons such as ethylene glycol, 1,3-propanediol, 1,2-propanediol, 1,4-butanediol, 1,3-butanediol, 1,2-butanediol, 1,5-heptanediol, 1,6-hexanediol, 1,9-nonanediol, 1,10-decanediol, and 1,12-dodecanediol; dihydroxy compounds of branched aliphatic hydrocarbons such as neopentyl glycol and hexylene glycol; and 1,2-cyclohexanediol. dihydroxy compounds which are secondary and tertiary alcohols of alicyclic hydrocarbons, such as 1,2-cyclohexanedimethanol, 1,3-cyclohexanedimethanol, 1,4-cyclohexanediol, 1,3-adamantanediol, hydrogenated bisphenol A, and 2,2,4,4-tetramethyl-1,3-cyclobutanediol; 1,2-cyclohexanedimethanol, 1,3-cyclohexanedimethanol, 1,4-cyclohexanedimethanol, tricyclodecane dimethanol, pentacyclopentadecanedimethanol, 2,6-decane dimethanol, dihydroxy compounds which are primary alcohols of alicyclic hydrocarbons, exemplified by dihydroxy compounds derived from terpene compounds, such as diphenyl dimethanol, 1,5-decalin dimethanol, 2,3-decalin dimethanol, 2,3-norbornane dimethanol, 2,5-norbornane dimethanol, 1,3-adamantanedimethanol, and limonene; oxyalkylene glycols, such as diethylene glycol, triethylene glycol, tetraethylene glycol, polyethylene glycol, and polypropylene glycol; dihydroxy compounds having a cyclic ether structure, such as isosorbide; dihydroxy compounds having a cyclic acetal structure, such as spiroglycol and dioxane glycol; alicyclic dicarboxylic acids, such as 1,2-cyclohexanedicarboxylic acid, 1,3-cyclohexanedicarboxylic acid, and 1,4-cyclohexanedicarboxylic acid; and aliphatic dicarboxylic acids, such as malonic acid, succinic acid, glutaric acid, adipic acid, pimelic acid, suberic acid, azelaic acid, and sebacic acid. Specific examples of compounds into which the structural unit containing an aromatic ring can be introduced are given below: 2,2-bis(4-hydroxyphenyl)propane, 2,2-bis(3-methyl-4-hydroxyphenyl)propane, 2,2-bis(4-hydroxy-3,5-dimethylphenyl)propane, 2,2-bis(4-hydroxy-3,5-diethylphenyl)propane, 2,2-bis(4-hydroxy-(3-phenyl)phenyl)propane, 2,2-bis(4-hydroxy-(3,5-diphenyl)phenyl)propane, 2,2-bis(4-hydroxy-3,5-dibromophenyl)propane, bis(4-hydroxyphenyl)propane, )methane, 1,1-bis(4-hydroxyphenyl)ethane, 2,2-bis(4-hydroxyphenyl)butane, 2,2-bis(4-hydroxyphenyl)pentane, 1,1-bis(4-hydroxyphenyl)-1-phenylethane, bis(4-hydroxyphenyl)diphenylmethane, 1,1-bis(4-hydroxyphenyl)-2-ethylhexane, 1,1-bis(4-hydroxyphenyl)decane, bis(4-hydroxy-3-nitrophenyl)methane, 3,3-bis(4-hydroxyphenyl)pentane, 1,3-bis(4-hydroxyphenyl)pentane, Bis(2-(4-hydroxyphenyl)-2-propyl)benzene, 1,3-bis(2-(4-hydroxyphenyl)-2-propyl)benzene, 2,2-bis(4-hydroxyphenyl)hexafluoropropane, 1,1-bis(4-hydroxyphenyl)cyclohexane, bis(4-hydroxyphenyl)sulfone, 2,4'-dihydroxydiphenyl sulfone, bis(4-hydroxyphenyl)sulfide, bis(4-hydroxy-3-methylphenyl)sulfide, bis(4-hydroxyphenyl)disulfide, 4, Aromatic bisphenol compounds such as 4'-dihydroxydiphenyl ether and 4,4'-dihydroxy-3,3'-dichlorodiphenyl ether; dihydroxy compounds having an ether group bonded to an aromatic group such as 2,2-bis(4-(2-hydroxyethoxy)phenyl)propane, 2,2-bis(4-(2-hydroxypropoxy)phenyl)propane, 1,3-bis(2-hydroxyethoxy)benzene, 4,4'-bis(2-hydroxyethoxy)biphenyl, and bis(4-(2-hydroxyethoxy)phenyl)sulfone;Aromatic dicarboxylic acids such as terephthalic acid, phthalic acid, isophthalic acid, 4,4'-diphenyldicarboxylic acid, 4,4'-diphenyletherdicarboxylic acid, 4,4'-benzophenonedicarboxylic acid, 4,4'-diphenoxyethanedicarboxylic acid, 4,4'-diphenylsulfonedicarboxylic acid, 2,6-naphthalenedicarboxylic acid, etc.; The aliphatic dicarboxylic acid and aromatic dicarboxylic acid components listed above can be used as the raw materials for the polyester carbonate as dicarboxylic acids themselves, but depending on the production method, dicarboxylic acid esters such as methyl esters and phenyl esters, and dicarboxylic acid derivatives such as dicarboxylic acid halides can also be used as raw materials.
[0043] As copolymerization monomers, dihydroxy compounds having a fluorene ring, such as 9,9-bis(4-(2-hydroxyethoxy)phenyl)fluorene, 9,9-bis(4-hydroxyphenyl)fluorene, and 9,9-bis(4-hydroxy-3-methylphenyl)fluorene, which are conventionally known as compounds having structural units with negative birefringence, and dicarboxylic acid compounds having a fluorene ring can also be used in combination with oligofluorene compounds.
[0044] Of the structural units that can be introduced by the compound having an alicyclic structure, the resin used in the present invention preferably contains a structural unit represented by the following formula (3) as a copolymerization component. [ka]
[0045] As a dihydroxy compound capable of introducing the structural unit of the above formula (3), spiroglycol can be used.
[0046] In the resin used in the present invention, the structural unit represented by the formula (3) is preferably contained in an amount of 5% by mass or more and 90% by mass or less. The upper limit is more preferably 70% by mass or less, and particularly preferably 50% by mass or less. The lower limit is more preferably 10% by mass or more, more preferably 20% by mass or more, and particularly preferably 25% by mass or more. If the content of the structural unit represented by the formula (3) is equal to or more than the lower limit, sufficient mechanical properties, heat resistance, and low photoelastic coefficient can be obtained. Furthermore, compatibility with acrylic resins is improved, and the transparency of the obtained resin composition can be further improved. In addition, since the polymerization reaction rate of spiroglycol is relatively slow, the polymerization reaction can be easily controlled by suppressing the content to the upper limit or less.
[0047] The resin used in the present invention preferably further contains a structural unit represented by the following formula (4) as a copolymerization component. [ka]
[0048] Dihydroxy compounds capable of introducing the structural unit represented by the formula (4) include isosorbide (ISB), isomannide, and isoidite, which are stereoisomeric. These may be used alone or in combination of two or more.
[0049] In the resin used in the present invention, the structural unit represented by the formula (4) is preferably contained in an amount of 5% by mass or more and 90% by mass or less. The upper limit is more preferably 70% by mass or less, and particularly preferably 50% by mass or less. The lower limit is more preferably 10% by mass or more, and particularly preferably 15% by mass or more. If the content of the structural unit represented by the formula (4) is equal to or more than the lower limit, sufficient mechanical properties, heat resistance, and low photoelastic coefficient can be obtained. In addition, since the structural unit represented by the formula (4) has a high water absorption property, if the content of the structural unit represented by the formula (4) is equal to or less than the upper limit, the dimensional change of the molded body due to water absorption can be suppressed within an acceptable range.
[0050] The resin used in the present invention may further contain other structural units. Such structural units may be referred to as "other structural units". As monomers having other structural units, it is more preferable to adopt 1,4-cyclohexanedimethanol, tricyclodecane dimethanol, and 1,4-cyclohexanedicarboxylic acid (and derivatives thereof), and 1,4-cyclohexanedimethanol and tricyclodecane dimethanol are particularly preferable. Resins containing structural units derived from these monomers have an excellent balance of optical properties, heat resistance, mechanical properties, and the like. In addition, since the polymerization reactivity of diester compounds is relatively low, it is preferable not to use diester compounds other than diester compounds containing oligofluorene structural units from the viewpoint of increasing reaction efficiency.
[0051] The glass transition temperature (Tg) of the resin used in the present invention is preferably 110°C or more and 160°C or less. The upper limit is more preferably 155°C or less, more preferably 150°C or less, and particularly preferably 145°C or less. The lower limit is more preferably 120°C or more, and particularly preferably 130°C or more. If the glass transition temperature is outside the above range, the heat resistance tends to deteriorate, and dimensional changes may occur after film formation, or the quality reliability under the conditions of use of the retardation film may deteriorate. On the other hand, if the glass transition temperature is excessively high, unevenness in the film thickness may occur during film formation, the film may become brittle, the stretchability may deteriorate, and the transparency of the film may be impaired.
[0052] Details of the composition and manufacturing method of the polycarbonate-based resin are described, for example, in International Publication No. WO 2015 / 159928 (mentioned above), the disclosure of which is incorporated herein by reference.
[0053] C-2-2.Acrylic resin As the acrylic resin, an acrylic resin as a thermoplastic resin is used. Examples of monomers that are structural units of the acrylic resin include the following compounds: methyl methacrylate, methacrylic acid, methyl acrylate, acrylic acid, benzyl (meth)acrylate, n-butyl (meth)acrylate, i-butyl (meth)acrylate, t-butyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, lauryl (meth)acrylate, tridecyl (meth)acrylate, stearyl (meth)acrylate, glycidyl (meth)acrylate, hydroxypropyl (meth)acrylate, 2-methoxyethyl (meth)acrylate, 2-ethoxyethyl (meth)acrylate, cyclohexyl (meth)acrylate, isobornyl (meth)acrylate, norbornyl (meth)acrylate, dicyclopentenyl (meth)acrylate, dicyclopentanyl (meth)acrylate, dicyclopentenyloxyethyl (meth)acrylate. Acrylate, tetrahydrofurfuryl (meth)acrylate, acrylic (meth)acrylate, 2-hydroxyethyl (meth)acrylate, 2-(meth)acryloyloxyethyl succinate, 2-(meth)acryloyloxyethyl maleate, 2-(meth)acryloyloxyethyl phthalate, 2-(meth)acryloyloxyethyl hexahydrophthalate, pentamethylpiperidyl (meth)acrylate, tetramethylpiperidyl (meth)acrylate, dimethylaminoethyl (meth)acrylate, diethylaminoethyl (meth)acrylate, cyclopentyl methacrylate, cyclopentyl acrylate, cyclohexyl methacrylate, cyclohexyl acrylate, cycloheptyl methacrylate, cycloheptyl acrylate, cyclooctyl methacrylate, cyclooctyl acrylate, cyclododecyl methacrylate, cyclododecyl acrylate. These may be used alone or in combination of two or more. The form of using two or more kinds of monomers in combination includes copolymerization of two or more kinds of monomers, blend of two or more homopolymers of one kind of monomer, and combinations thereof. Furthermore, other monomers copolymerizable with these acrylic monomers (e.g., olefin monomers, vinyl monomers) may be used in combination.
[0054] The acrylic resin contains a structural unit derived from methyl methacrylate. The content of the structural unit derived from methyl methacrylate in the acrylic resin is preferably 70% by mass or more and 100% by mass or less. The lower limit is more preferably 80% by mass or more, even more preferably 90% by mass or more, and particularly preferably 95% by mass or more. In this range, excellent compatibility with the polycarbonate resin of the present invention can be obtained. As structural units other than methyl methacrylate, it is preferable to use methyl acrylate, phenyl (meth)acrylate, benzyl (meth)acrylate, and styrene. By copolymerizing methyl acrylate, the thermal stability can be improved. Since the refractive index of the acrylic resin can be adjusted by using phenyl (meth)acrylate, benzyl (meth)acrylate, and styrene, the transparency of the obtained resin composition can be improved by matching it to the refractive index of the resin to be combined. By using such an acrylic resin, a reverse dispersion retardation film having excellent stretchability and retardation expression and small haze can be obtained.
[0055] The weight average molecular weight Mw of the acrylic resin is 10,000 or more and 200,000 or less. The lower limit is preferably 30,000 or more, and particularly preferably 50,000 or more. The upper limit is preferably 180,000 or less, and particularly preferably 150,000 or less. If the molecular weight is in such a range, compatibility with the polycarbonate resin can be obtained, and the transparency of the final retardation film (retardation layer) can be improved, and the effect of sufficiently improving the extensibility during stretching can be obtained. The weight average molecular weight is a molecular weight measured by GPC and converted into polystyrene. In addition, it is preferable that the acrylic resin does not substantially contain a branched structure from the viewpoint of compatibility. The absence of a branched structure can be confirmed by, for example, the GPC curve of the acrylic resin being monomodal.
[0056] C-2-3. Blends of polycarbonate resins and acrylic resins The polycarbonate resin or the like and the acrylic resin are blended, and the resin composition is subjected to a method for producing a retardation film (retardation layer) (the manufacturing method will be described later in Section C-3). The polycarbonate resin or the like and the acrylic resin can be blended preferably in a molten state. A representative method for blending in a molten state is melt kneading using an extruder. The kneading temperature (molten resin temperature) is preferably 200°C to 280°C, more preferably 220°C to 270°C, and even more preferably 230°C to 260°C. If the kneading temperature is in such a range, pellets of a resin composition in which both resins are uniformly blended can be obtained while suppressing thermal decomposition. If the molten resin temperature in the extruder exceeds 280°C, coloring and / or thermal decomposition of the resin may occur. On the other hand, if the molten resin temperature in the extruder is lower than 200°C, the resin viscosity may become too high, causing an excessive load on the extruder, or the resin may not be melted sufficiently. Any suitable configuration may be adopted for the configuration of the extruder, the configuration of the screw, etc. In order to obtain a resin with sufficient transparency for optical film applications, it is preferable to use a twin-screw extruder. Furthermore, since there is a concern that the remaining low molecular weight components in the resin and the low molecular weight thermally decomposed components during extrusion kneading may contaminate the cooling roll and the transport roll in the film-forming process and the stretching process, it is preferable to use an extruder equipped with a vacuum vent in order to remove them.
[0057] The content of the acrylic resin in the resin composition (as a result, the retardation layer) is 0.5% by mass or more and 2.0% by mass or less, as described above. The lower limit is more preferably 0.6% by mass or more. The upper limit is preferably 1.5% by mass or less, more preferably 1.0% by weight or less, even more preferably 0.9% by weight or less, and particularly preferably 0.8% by weight or less. In this way, by blending the acrylic resin in a very limited ratio with the polycarbonate resin, the stretchability and retardation expression can be significantly increased. Furthermore, haze can be suppressed. Such an effect is not theoretically clear, and is an unexpected excellent effect obtained by trial and error. If the content of the acrylic resin is too small, the above effect may not be obtained. On the other hand, if the content of the acrylic resin is too high, the haze may become high. In addition, the stretchability and retardation expression are often insufficient or even decreased compared to the case in the above range.
[0058] The resin composition may be further blended with synthetic resins such as aromatic polycarbonate, aliphatic polycarbonate, aromatic polyester, aliphatic polyester, polyamide, polystyrene, polyolefin, acrylic, amorphous polyolefin, ABS, AS, polylactic acid, polybutylene succinate, etc., rubber, and combinations thereof, for the purpose of improving properties such as mechanical properties and / or solvent resistance.
[0059] The resin composition may further contain additives. Specific examples of additives include heat stabilizers, antioxidants, catalyst deactivators, ultraviolet absorbers, light stabilizers, release agents, dyes and pigments, impact modifiers, antistatic agents, slip agents, lubricants, plasticizers, compatibilizers, nucleating agents, flame retardants, inorganic fillers, and foaming agents. The type, number, combination, and content of the additives contained in the resin composition may be appropriately set according to the purpose.
[0060] C-3. Method for forming retardation layer The retardation layer is obtained by forming a film from the resin composition described in the above item C-2, and further stretching the film. Any appropriate molding method can be adopted as a method for forming a film from the resin composition. Specific examples include compression molding, transfer molding, injection molding, extrusion molding, blow molding, powder molding, FRP molding, cast coating (for example, casting), calendar molding, and heat pressing. Among them, extrusion molding or cast coating, which can improve the smoothness of the obtained film and obtain good optical uniformity, is preferable. Since the cast coating method may cause problems due to residual solvent, extrusion molding is particularly preferable, and melt extrusion molding using a T-die is particularly preferable from the viewpoint of film productivity and ease of subsequent stretching treatment. The molding conditions can be appropriately set according to the composition and type of the resin used, the properties desired for the retardation layer, and the like. In this way, a resin film containing a polycarbonate-based resin and an acrylic resin can be obtained.
[0061] The thickness of the resin film (unstretched film) can be set to any appropriate value depending on the desired thickness of the resulting retardation layer, the desired optical properties, the stretching conditions described below, etc. It is preferably 50 μm to 300 μm.
[0062] The stretching may be performed using any suitable stretching method and conditions (e.g., stretching temperature, stretching ratio, stretching direction). Specifically, various stretching methods such as free end stretching, fixed end stretching, free end shrinkage, and fixed end shrinkage may be used alone, simultaneously, or sequentially. The stretching may be performed in various directions or dimensions, such as the length direction, width direction, thickness direction, and oblique direction.
[0063] By appropriately selecting the stretching method and stretching conditions, it is possible to obtain a retardation layer having the desired optical properties (for example, refractive index properties, in-plane retardation, Nz coefficient).
[0064] In one embodiment, the stretching temperature of the film is a temperature equal to or lower than the glass transition temperature (Tg) of the polycarbonate resin or the like. Usually, when stretching a film of a polycarbonate resin or the like, the film is in a glass state at a temperature equal to or lower than the Tg, so that stretching is substantially impossible. According to the resin film used in the embodiment of the present invention, by blending a small amount of an acrylic resin (typically, polymethyl methacrylate), stretching at or below the Tg is possible without substantially changing the Tg of the polycarbonate resin or the like. Furthermore, although it is not theoretically clear, by performing stretching at or below the Tg, a reverse dispersion retardation film (retardation layer) excellent in stretchability and retardation expression and small haze can be realized. Specifically, the stretching temperature is preferably Tg to Tg-10°C, more preferably Tg to Tg-8°C, and even more preferably Tg to Tg-5°C. The film can be appropriately stretched even at a temperature higher than Tg, for example, up to about Tg+5°C, or, for example, up to about Tg+2°C.
[0065] The stretched film obtained as described above is preferably subjected to a heat treatment at a temperature of 105° C. or higher for 2 minutes or more. By carrying out the heat treatment, a retardation layer having the desired shrinkage ratio can be formed. The heating temperature is preferably 105° C. to 140° C., more preferably 110° C. to 130° C., and even more preferably 115° C. to 125° C. The heating time is preferably 2 minutes to 150 minutes, more preferably 3 minutes to 120 minutes, and even more preferably 5 minutes to 60 minutes.
[0066] If necessary, the stretched film may be subjected to a relaxation treatment. This can relax the stress caused by the stretching, and a retardation layer having the desired shrinkage ratio can be formed. Any appropriate conditions can be adopted as the relaxation treatment conditions. For example, the stretched film is shrunk along the stretching direction at a predetermined relaxation temperature and a predetermined relaxation ratio (shrinkage ratio). The relaxation temperature is preferably 60°C to 150°C. The relaxation ratio is preferably 3% to 6%. When the relaxation treatment is performed, the relaxation treatment can be typically performed before the heat treatment.
[0067] In this manner, a retardation film constituting a retardation layer can be obtained.
[0068] D. First Adhesive Layer and Second Adhesive Layer D-1. Characteristics of the first adhesive layer and / or the second adhesive layer As described above, the first adhesive layer 20 has a glue slippage of 300 μm or more after a heating test at 85° C. for 500 hours, preferably 330 μm or more, more preferably 360 μm or more, even more preferably 390 μm or more, and particularly preferably 420 μm or more. The upper limit of the glue slippage may be, for example, 600 μm. By using an adhesive having a large glue slippage to bond the polarizer and the retardation layer, a retardation layer and a polarizing plate with a glue layer attached thereto in which retardation unevenness in a high temperature environment is suppressed can be realized due to the synergistic effect of the effect of controlling the shrinkage rate in the slow axis direction of the retardation layer and the effect of controlling the creep value of the second adhesive layer described later. In this specification, the term "glue slippage amount" refers to the length of the largest protruding part of the adhesive layer protruding from the end faces of the polarizer and the retardation layer in the retardation layer and the polarizing plate with a glue layer attached thereto after a heating test.
[0069] The second adhesive layer 40 has a creep value at 23°C of, for example, 5 μm or more, preferably 20 μm or more, more preferably 30 μm or more, even more preferably 60 μm or more, particularly preferably 100 μm or more, and particularly preferably 120 μm or more. The upper limit of the creep value can be, for example, 300 μm. By using an adhesive having such a large creep value to bond the retardation layer and the adhesive layer-attached polarizing plate to the image display cell, an image display device in which color unevenness in a high temperature environment is suppressed can be realized due to the synergistic effect of the effect of controlling the shrinkage rate in the slow axis direction of the retardation layer and the effect of controlling the amount of adhesive slippage of the first adhesive layer. The creep value can be measured, for example, by the following procedure: A test sample cut out from an adhesive sheet is attached to a support plate at a bonding surface of 10 mm x 10 mm. With the support plate to which the test sample is attached fixed, a load of 500 gf is applied vertically downward. The amount of displacement from the support plate was measured 1 second and 3600 seconds after the load was applied, and Cr1 and Cr2 were measured, respectively. 3600 Let Cr1 and Cr 3600 The creep value is determined as ΔCr by the following formula: Note that the creep value in this specification is a value calculated based on a pressure-sensitive adhesive layer thickness of 20 μm. ΔCr=Cr 3600 -Cr1
[0070] The first pressure-sensitive adhesive layer and / or the second pressure-sensitive adhesive layer preferably have a storage modulus at 85° C. of 1.0×10 4 Pa or more, preferably 2.0×10 4 Pa or more, more preferably 5.0×10 4 Pa or more, and more preferably 1.0×10 5 If the storage modulus is within this range, it is easy to achieve the desired adhesive slippage and / or creep value. On the other hand, the storage modulus is, for example, 3.0×10 6 Pa or less.
[0071] The thickness of the first pressure-sensitive adhesive layer is preferably 2 μm to 50 μm, more preferably 3 μm to 40 μm. The thickness of the second pressure-sensitive adhesive layer is preferably 4 μm to 30 μm, more preferably 5 μm to 20 μm. If the thicknesses of the first pressure-sensitive adhesive layer and the second pressure-sensitive adhesive layer are within such ranges, a retardation layer and a pressure-sensitive adhesive layer-attached polarizing plate in which retardation unevenness in a high-temperature environment is suppressed can be realized due to a synergistic effect with the effect of controlling the adhesive slippage amount and creep value, and an image display device in which color unevenness in a high-temperature environment is suppressed can be realized.
[0072] D-2. Materials for the first adhesive layer and the second adhesive layer The first adhesive layer and the second adhesive layer may have any suitable configuration as long as the first adhesive layer has the desired adhesive slippage amount and the second adhesive layer has the desired creep value. The first adhesive layer and the second adhesive layer may be made of the same adhesive, or may be made of different adhesives. Hereinafter, the first adhesive layer and the second adhesive layer are collectively referred to as the adhesive layer, and the constituent materials are described. The adhesive slippage amount and / or creep value can be controlled by adjusting the composition (e.g., type (polarity, Tg, softness), molecular weight of the base polymer) and crosslinking structure (e.g., type of crosslinking agent, distance between crosslinking points (molecular weight between crosslinking points), crosslinking density) of the adhesive constituting the adhesive layer.
[0073] D-2-1. Base polymer The pressure-sensitive adhesive layer is typically formed from a pressure-sensitive adhesive composition containing a (meth)acrylic polymer, a urethane polymer, a silicone polymer, or a rubber polymer as a base polymer. When a (meth)acrylic polymer is used as the base polymer, the pressure-sensitive adhesive layer is formed from a pressure-sensitive adhesive composition containing, for example, a (meth)acrylic polymer (A). The (meth)acrylic polymer (A) contains an alkyl (meth)acrylate as a main component.
[0074] <(Meth)acrylic polymer (A)> As described above, the (meth)acrylic polymer (A) contains an alkyl (meth)acrylate as a main component. From the viewpoint of improving the adhesiveness of the pressure-sensitive adhesive layer, the alkyl (meth)acrylate is preferably 50% by weight or more of the total monomer components forming the (meth)acrylic polymer (A), and can be arbitrarily set as the remainder of the monomer other than the alkyl (meth)acrylate. Here, (meth)acrylate refers to acrylate and / or methacrylate.
[0075] The alkyl (meth)acrylate constituting the main skeleton of the (meth)acrylic polymer (A) may be a linear or branched alkyl group having 1 to 18 carbon atoms. Examples of the alkyl group include a methyl group, an ethyl group, a propyl group, an isopropyl group, a butyl group, an isobutyl group, an amyl group, a hexyl group, a cyclohexyl group, a heptyl group, a 2-ethylhexyl group, an isooctyl group, a nonyl group, a decyl group, an isodecyl group, a dodecyl group, an isomyristyl group, a lauryl group, a tridecyl group, a pentadecyl group, a hexadecyl group, a heptadecyl group, and an octadecyl group. The alkyl (meth)acrylate may be used alone or in combination. The average carbon number of the alkyl group is preferably 3 to 10.
[0076] The (meth)acrylic polymer (A) may contain, as a monomer component, a copolymerizable monomer such as a carboxyl group-containing monomer (a1) or a hydroxyl group-containing monomer (a2) in addition to the alkyl (meth)acrylate. The copolymerizable monomers may be used alone or in combination.
[0077] The carboxyl group-containing monomer (a1) is a compound that contains a carboxyl group in its structure and a polymerizable unsaturated double bond such as a (meth)acryloyl group or a vinyl group. Examples of the carboxyl group-containing monomer include (meth)acrylic acid, carboxyethyl (meth)acrylate, carboxypentyl (meth)acrylate, itaconic acid, maleic acid, fumaric acid, and crotonic acid. Among these, acrylic acid is preferred from the viewpoints of copolymerizability, cost, and improving the adhesive properties of the adhesive layer.
[0078] When a carboxyl group-containing monomer (a1) is used as a monomer component, the content of the carboxyl group-containing monomer (a1) is usually 0.01% by weight or more and 10% by weight or less in all monomer components forming the (meth)acrylic polymer (A).
[0079] The hydroxyl group-containing monomer (a2) is a compound that contains a hydroxyl group in its structure and a polymerizable unsaturated double bond such as a (meth)acryloyl group or a vinyl group. Examples of the hydroxyl group-containing monomer include hydroxyalkyl (meth)acrylates such as 2-hydroxyethyl (meth)acrylate, 3-hydroxypropyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, 6-hydroxyhexyl (meth)acrylate, 8-hydroxyoctyl (meth)acrylate, 10-hydroxydecyl (meth)acrylate, and 12-hydroxylauryl (meth)acrylate; (4-hydroxymethylcyclohexyl)-methyl acrylate, etc. Among these, from the viewpoint of improving the durability of the adhesive layer, 2-hydroxyethyl (meth)acrylate and 4-hydroxybutyl (meth)acrylate are preferred, and 4-hydroxybutyl (meth)acrylate is more preferred.
[0080] When the hydroxyl group-containing monomer (a2) is used as a monomer component, the content of the hydroxyl group-containing monomer (a2) is usually 0.01% by weight or more and 10% by weight or less in all the monomer components forming the (meth)acrylic polymer (A).
[0081] The (meth)acrylic polymer (A) preferably contains, as a monomer component, a monomer having an unsaturated carbon-carbon double bond that results in a homopolymer having a glass transition temperature of 0° C. or higher. Examples of the monomer (a3) having an unsaturated carbon-carbon double bond that results in a homopolymer having a glass transition temperature of 0° C. or higher include alkyl (meth)acrylate monomers and (meth)acrylic acid. The monomer (a3) is preferably a monomer having an unsaturated carbon-carbon double bond that results in a homopolymer having a glass transition temperature of 20° C. or higher, and more preferably a monomer having an unsaturated carbon-carbon double bond that results in a homopolymer having a glass transition temperature of 40° C. or higher.
[0082] In the (meth)acrylic polymer (A), the content of the monomer (a3) is not particularly limited. The content is usually 0.1% by weight to 40% by weight, more preferably 1% by weight to 30% by weight. When two or more kinds of the monomer (a3) are used in combination, the content is the total content.
[0083] Examples of the monomer (a3) include methyl acrylate (Tg: 8° C.), methyl methacrylate (Tg: 105° C.), ethyl methacrylate (Tg: 65° C.), n-propyl acrylate (Tg: 3° C.), n-propyl methacrylate (Tg: 35° C.), n-pentyl acrylate (Tg: 22° C.), n-tetradecyl acrylate (Tg: 24° C.), n-hexadecyl acrylate (Tg: 35° C.), n-hexadecyl methacrylate (Tg: 15° C.), n-stearyl acrylate (Tg: 30° C.), and n-stearyl methacrylate (Tg: 38° C.). Linear alkyl (meth)acrylates; branched alkyl (meth)acrylates such as t-butyl acrylate (Tg: 43°C), t-butyl methacrylate (Tg: 48°C), i-propyl methacrylate (Tg: 81°C), and i-butyl methacrylate (Tg: 48°C); cyclic alkyl (meth)acrylates such as cyclohexyl acrylate (Tg: 19°C), cyclohexyl methacrylate (Tg: 65°C), isobornyl acrylate (Tg: 94°C), and isobornyl methacrylate (Tg: 180°C); acrylic acid (Tg: 106°C), etc. These can be used alone or in combination.
[0084] When the pressure-sensitive adhesive composition contains a crosslinking agent described later, the copolymerization monomer becomes a reaction site with the crosslinking agent. Carboxyl group-containing monomers and hydroxyl group-containing monomers are highly reactive with intermolecular crosslinking agents, and are preferably used to improve the cohesiveness and heat resistance of the resulting pressure-sensitive adhesive layer. In addition, carboxyl group-containing monomers are preferred in terms of achieving both durability and reworkability, and hydroxyl group-containing monomers are preferred in terms of improving reworkability.
[0085] Other copolymerizable monomers (a4) may be further used as monomer components. The other copolymerizable monomers (a4) have a polymerizable functional group having an unsaturated double bond, such as a (meth)acryloyl group or a vinyl group. By using the other copolymerizable monomers (a4), the adhesiveness and heat resistance of the pressure-sensitive adhesive layer can be improved. The other copolymerizable monomers (a4) can be used alone or in combination.
[0086] The adhesion of the pressure-sensitive adhesive layer can be improved by using an amino group-containing monomer or an amide group-containing monomer as the other copolymerizable monomer (a4). Examples of the amino group-containing monomer include N,N-dimethylaminoethyl (meth)acrylate and N,N-dimethylaminopropyl (meth)acrylate. Examples of the amide group-containing monomer include acrylamide-based monomers such as (meth)acrylamide, N,N-dimethyl(meth)acrylamide, N,N-diethyl(meth)acrylamide, N-isopropylacrylamide, N-methyl(meth)acrylamide, N-butyl(meth)acrylamide, N-hexyl(meth)acrylamide, N-methylol(meth)acrylamide, N-methylol-N-propane(meth)acrylamide, aminomethyl(meth)acrylamide, aminoethyl(meth)acrylamide, mercaptomethyl(meth)acrylamide, and mercaptoethyl(meth)acrylamide; N-acryloyl heterocyclic monomers such as N-(meth)acryloylmorpholine, N-(meth)acryloylpiperidine, and N-(meth)acryloylpyrrolidine; and N-vinyl group-containing lactam monomers such as N-vinylpyrrolidone and N-vinyl-ε-caprolactam.
[0087] The other copolymerization monomer (a4) may be a polyfunctional monomer. The use of a polyfunctional monomer allows the adjustment of the gel fraction of the adhesive layer and the control of the cohesive force. Examples of the polyfunctional monomer include polyfunctional acrylates such as hexanediol di(meth)acrylate (1,6-hexanediol di(meth)acrylate), butanediol di(meth)acrylate, (poly)ethylene glycol di(meth)acrylate, (poly)propylene glycol di(meth)acrylate, neopentyl glycol di(meth)acrylate, pentaerythritol di(meth)acrylate, pentaerythritol tri(meth)acrylate, dipentaerythritol hexa(meth)acrylate, trimethylolpropane tri(meth)acrylate, tetramethylolmethane tri(meth)acrylate, allyl (meth)acrylate, vinyl (meth)acrylate, epoxy acrylate, polyester acrylate, and urethane acrylate; and divinylbenzene. The polyfunctional acrylate is preferably 1,6-hexanediol diacrylate or dipentaerythritol hexa(meth)acrylate.
[0088] Examples of the other copolymerizable monomers (a4), in addition to those mentioned above, include (meth)acrylic acid alkoxyalkyl esters such as 2-methoxyethyl (meth)acrylate, 2-ethoxyethyl (meth)acrylate, methoxytriethylene glycol (meth)acrylate, 3-methoxypropyl (meth)acrylate, 3-ethoxypropyl (meth)acrylate, 4-methoxybutyl (meth)acrylate, and 4-ethoxybutyl (meth)acrylate; cyclopolymerizable monomers such as methyl 2-(allyloxymethyl)acrylate; epoxy group-containing monomers such as glycidyl (meth)acrylate and methyl glycidyl (meth)acrylate; and sulfonic acid group-containing monomers such as sodium vinyl sulfonate. monomers; phosphate group-containing monomers; (meth)acrylic acid esters having an alicyclic hydrocarbon group, such as cyclopentyl (meth)acrylate, cyclohexyl (meth)acrylate, isobornyl (meth)acrylate, etc.; (meth)acrylic acid esters having an aromatic hydrocarbon group, such as phenyl (meth)acrylate, phenoxyethyl (meth)acrylate, benzyl (meth)acrylate, etc.; vinyl esters such as vinyl acetate, vinyl propionate, etc.; aromatic vinyl compounds such as styrene, vinyl toluene, etc.; olefins or dienes such as ethylene, propylene, butadiene, isoprene, isobutylene, etc.; vinyl ethers such as vinyl alkyl ethers; and vinyl chloride.
[0089] The content of the other copolymerizable monomer (a4) in the (meth)acrylic polymer is preferably 20% by mass or less, more preferably 10% by mass or less, even more preferably 8% by mass or less, and particularly preferably 5% by mass or less.
[0090] The weight average molecular weight Mw of the (meth)acrylic polymer (A) is, for example, 200,000 to 3,000,000, preferably 1,000,000 to 2,500,000, and more preferably 1,200,000 to 2,500,000. If the weight average molecular weight Mw is within this range, a pressure-sensitive adhesive layer having excellent durability (particularly, heat resistance) can be obtained. If the weight average molecular weight Mw exceeds 3,000,000, an increase in viscosity and / or gelation during polymer polymerization may occur.
[0091] D-2-2. Silane coupling agents containing reactive functional groups The pressure-sensitive adhesive composition may contain a reactive functional group-containing silane coupling agent. The reactive functional group of the reactive functional group-containing silane coupling agent is typically a functional group other than an acid anhydride group. Examples of functional groups other than an acid anhydride group include an epoxy group, a mercapto group, an amino group, an isocyanate group, an isocyanurate group, a vinyl group, a styryl group, an acetoacetyl group, a ureido group, a thiourea group, a (meth)acrylic group, a heterocyclic group, and combinations thereof. The reactive functional group-containing silane coupling agents may be used alone or in combination.
[0092] When a reactive functional group-containing silane coupling agent is blended in the pressure-sensitive adhesive composition, the blending amount of the reactive functional group-containing silane coupling agent is usually 0.001 parts by weight or more and 5 parts by weight or less per 100 parts by weight of the (meth)acrylic polymer (A).
[0093] D-2-3. Crosslinking agent The pressure-sensitive adhesive composition may contain a crosslinking agent. As the crosslinking agent, an organic crosslinking agent, a polyfunctional metal chelate, etc. may be used. As the organic crosslinking agent, for example, an isocyanate crosslinking agent, a peroxide crosslinking agent, an epoxy crosslinking agent, and an imine crosslinking agent may be mentioned. The polyfunctional metal chelate is a crosslinking agent in which a polyvalent metal is covalently bonded or coordinately bonded to an organic compound. When the pressure-sensitive adhesive composition is a radiation curing type, a polyfunctional monomer may be used as the crosslinking agent. The crosslinking agents may be used alone or in combination.
[0094] When a crosslinking agent is blended in the pressure-sensitive adhesive composition, the blending amount of the crosslinking agent is usually 0.01 parts by weight or more and 15 parts by weight or less based on 100 parts by weight of the (meth)acrylic polymer (A).
[0095] When an isocyanate-based crosslinking agent is blended in the pressure-sensitive adhesive composition, the blending amount of the isocyanate-based crosslinking agent is usually 0.01 parts by weight or more and 15 parts by weight or less based on 100 parts by weight of the (meth)acrylic polymer.
[0096] When a peroxide is blended in the pressure-sensitive adhesive composition, the blending amount of the peroxide is usually 0.01 to 2 parts by weight based on 100 parts by weight of the (meth)acrylic polymer. Within this range, it is easy to adjust the processability and crosslinking stability.
[0097] D-2-4.Additives The adhesive composition may contain a (meth)acrylic oligomer and / or an ionic compound. The adhesive composition may also contain an additive. Specific examples of additives include colorants, powders such as pigments, dyes, surfactants, plasticizers, tackifiers, surface lubricants, leveling agents, softeners, antioxidants, antiaging agents, light stabilizers, UV absorbers, polymerization inhibitors, inorganic or organic fillers, metal powders, particles, and foils. A redox system may also be used by adding a reducing agent within a controllable range. The type, number, combination, and content of additives may be appropriately set according to the purpose. The content of additives is preferably 5 parts by weight or less, more preferably 3 parts by weight or less, and even more preferably 1 part by weight or less, based on 100 parts by weight of the (meth)acrylic polymer (A).
[0098] E. Image display device The retardation layer and the pressure-sensitive adhesive layer-attached polarizing plate described in the above items A to D can be applied to an image display device. Therefore, the embodiment of the present invention also includes an image display device using such a retardation layer and a pressure-sensitive adhesive layer-attached polarizing plate. Representative examples of the image display device include a liquid crystal display device and an organic EL display device. The image display device according to the embodiment of the present invention typically includes the retardation layer and the pressure-sensitive adhesive layer-attached polarizing plate described in the above items A to D on the viewing side. EXAMPLES
[0099] The present invention will be described in detail below with reference to examples, but the present invention is not limited to these examples. The methods for measuring the various properties are as follows.
[0100] (1) Amount of adhesive shift The polarizing plates with retardation layer and adhesive layer obtained in the examples and comparative examples were cut to a predetermined size (M size or T size in Table 1 described later) to prepare test samples. The test samples were subjected to a heating test at 85°C for 500 hours, and the amount of the first adhesive layer protruding from the end faces of the polarizer and retardation layer after the heating test was observed and measured using an objective lens (20x). The length of the part of the first adhesive layer that protruded the most was taken as the amount of adhesive slippage. During observation, the transmitted light was set to 0 (zero) and the observation was adjusted to be performed using reflected light. (2) Creep value The polarizing plates with retardation layers and adhesive layers obtained in the examples and comparative examples were cut into a size of 10 mm x 30 mm to prepare test samples. The upper end portion of the test sample (10 mm x 10 mm) was attached to a SUS plate via a second adhesive layer, and a load of 500 gf was applied vertically downward to the lower end portion of the test sample. The amount of deviation between the test sample and the SUS plate was measured 1 second and 3600 seconds after the load was applied, and the deviations were calculated as Cr1 and Cr 3600 Cr1 and Cr 3600 The creep value was determined as ΔCr by the following formula: ΔCr=Cr 3600 -Cr1 (3) Color unevenness The polarizing plate with the retardation layer and the adhesive layer obtained in the examples and comparative examples was cut to a predetermined size (M size or T size in Table 1 described later) and attached to a glass plate via a second adhesive layer to prepare a test sample. The test sample was heated at 85°C for 500 hours and then placed on a reflective sheet (DMS deposition film, manufactured by Toray Film Processing Co., Ltd.), and the reflection hue a at the center of the sample was measured using a spectrophotometer (product name "CM-2600d" manufactured by Konica Minolta, Inc.). * C and b * C , and the reflection hue a at the end of the sample * E and b * E The value of Δab calculated by the following formula was used as an index of color unevenness. The smaller the Δab, the better the color unevenness. Δab={(a * E-a * C ) 2 +(b * E -b * C ) 2} 1 / 2
[0101] [Compound abbreviation] The abbreviations for the compounds used in the following Production Examples are as follows. BPFM: Bis[9-(2-phenoxycarbonylethyl)fluoren-9-yl]methane It was synthesized by the method described in JP 2015-25111 A. [ka] ISB: Isosorbide [Rocket Fleuret] SPG: Spiroglycol [Mitsubishi Gas Chemical Co., Ltd.] DPC: Diphenyl carbonate [Mitsubishi Chemical Corporation]
[0102] [Production Example 1: Preparation of Retardation Film Constituting Retardation Layer] Polymerization was carried out using a batch polymerization apparatus consisting of two vertical stirring reactors equipped with a stirring blade and a reflux condenser. BPFM was 30.31 parts by mass (0.047 mol), ISB was 39.94 parts by mass (0.273 mol), SPG was 30.20 parts by mass (0.099 mol), DPC was 69.67 parts by mass (0.325 mol), and calcium acetate monohydrate was 7.88 × 10 as a catalyst. -4 Part of mass (4.47×10 -6mol) was charged. After the inside of the reactor was purged with nitrogen under reduced pressure, heating was performed with a heat medium, and stirring was started when the inside temperature reached 100 ° C. 40 minutes after the start of the temperature increase, the inside temperature was reached 220 ° C., and while controlling to maintain this temperature, the pressure was simultaneously reduced, and 90 minutes after reaching 220 ° C., the pressure was reduced to 13.3 kPa. Phenol vapor by-produced with the polymerization reaction was led to a reflux condenser at 110 ° C., a small amount of monomer components contained in the phenol vapor were returned to the reactor, and the uncondensed phenol vapor was led to a condenser at 45 ° C. and recovered. Nitrogen was introduced into the first reactor to restore the pressure to atmospheric pressure, and the oligomerized reaction liquid in the first reactor was transferred to the second reactor. Next, the temperature increase and pressure reduction in the second reactor were started, and the inside temperature was set to 240 ° C. and the pressure was set to 20 kPa in 40 minutes. Thereafter, the polymerization was allowed to proceed while further reducing the pressure until the specified stirring power was reached. When the specified power was reached, nitrogen was introduced into the reactor to restore pressure, and the polyester carbonate produced was extruded into water and cut into strands to obtain pellets. This resin is called "PC1". The ratio of structural units derived from each monomer is BPFM / ISB / SPG / DPC=21.5 / 39.4 / 30.0 / 9.1% by mass. PC1 has a reduced viscosity of 0.46 dL / g, Mw of 48,000, and a refractive index n D is 1.526, the melt viscosity is 2480 Pa s, the glass transition temperature is 139°C, and the photoelastic coefficient is 9×10 -12 [m 2 / N], and the wavelength dispersion Re(450) / Re(550) was 0.85.
[0103] The obtained polyester carbonate was extrusion-kneaded with Dianale BR80 (manufactured by Mitsubishi Chemical Corporation) as an acrylic resin. A mixture of polycarbonate pellets (99.5 parts by mass) and BR80 powder (0.5 parts by mass) was fed into a twin-screw extruder TEX30HSS manufactured by Japan Steel Works, Ltd. using a quantitative feeder. The extruder cylinder temperature was set to 250°C, and extrusion was performed at a processing rate of 12 kg / hr and a screw rotation speed of 120 rpm. The extruder was also equipped with a vacuum vent, and the molten resin was extruded while being degassed under reduced pressure. The pellets of the resin composition thus obtained were vacuum-dried at 100°C for 6 hours or more, and then a long unstretched film having a length of 3 m, a width of 200 mm, and a thickness of 100 μm was produced using a film-making device equipped with a single-screw extruder (manufactured by Isuzu Chemical Engineering Co., Ltd., screw diameter 25 mm, cylinder set temperature: 250°C), a T-die (width 300 mm, set temperature: 220°C), a chill roll (set temperature: 120 to 130°C) and a winder. This long unstretched film was stretched at a stretching temperature of Tg and a stretch ratio of 2.4 times. The obtained stretched film was subjected to a relaxation treatment (relaxation temperature 130°C, relaxation rate 4.5%) and then subjected to a heat treatment at 125°C for 2 minutes.
[0104] In this way, a retardation film R1 constituting a retardation layer was obtained. The retardation film R1 had a shrinkage rate of 2.92% in the slow axis direction when heated at 125°C for 180 minutes. The retardation film R1 also showed a refractive index characteristic of nx>ny>nz, Re(550) was 145 nm, and Re(450) / Re(550) was 0.85.
[0105] [Production Example 2: Preparation of Retardation Film Constituting Retardation Layer] A retardation film R2 was obtained in the same manner as in Production Example 1, except that the relaxation treatment and heat treatment were not performed. The shrinkage rate in the slow axis direction of retardation film R2 when heated at 125°C for 180 minutes was 4.54%. In addition, retardation film R2 showed refractive index characteristics of nx>ny>nz, Re(550) was 145 nm, and Re(450) / Re(550) was 0.85.
[0106] [Production Example 3: Preparation of adhesive] (Preparation of Acrylic Polymer A1) A monomer mixture containing 99 parts of butyl acrylate and 1 part of 4-hydroxybutyl acrylate was charged into a four-neck flask equipped with a stirring blade, a thermometer, a nitrogen gas inlet tube, and a condenser. Furthermore, 0.1 parts of 2,2'-azobisisobutyronitrile as a polymerization initiator was charged together with 100 parts of ethyl acetate for 100 parts of this monomer mixture, and nitrogen gas was introduced to replace the atmosphere with nitrogen while gently stirring. The liquid temperature in the flask was kept at about 55°C, and a polymerization reaction was carried out for 8 hours to prepare a solution of acrylic polymer A1 with a weight average molecular weight (Mw) of 1.8 million and Mw / Mn=4.8.
[0107] (Preparation of Adhesive) 0.02 parts of trimethylolpropane / xylylene diisocyanate adduct (manufactured by Tosoh Corporation, product name "Takenate D110N"), 0.3 parts of peroxide crosslinking agent (manufactured by Nippon Oil & Fats Corporation, product name "Niper BMT"), and 0.2 parts of epoxy group-containing silane coupling agent (manufactured by Shin-Etsu Chemical Co., Ltd., product name "KBM-403") were blended with 100 parts of the solid content of the acrylic polymer A1 solution to obtain adhesive PSA1.
[0108] [Production Example 4: Preparation of adhesive] A pressure sensitive adhesive PSA2 was obtained in the same manner as in Production Example 3, except that the amount of D110N was changed to 0.1 part.
[0109] [Production Example 5: Preparation of adhesive] (Preparation of Acrylic Polymer A2) A solution of acrylic polymer A2 having Mw of 2.3 million and Mw / Mn of 3.9 was prepared in the same manner as in Production Example 3, except that a monomer mixture containing 94.9 parts of butyl acrylate, 0.1 parts of 2-hydroxyethyl acrylate and 5 parts of acrylic acid was used.
[0110] (Preparation of Adhesive) 0.6 parts of trimethylolpropane / tolylene diisocyanate adduct (manufactured by Tosoh Corporation, product name "Coronate L"), 0.2 parts of a peroxide crosslinking agent (manufactured by Nippon Oil & Fats Corporation, product name "Niper BMT"), and 0.2 parts of an epoxy group-containing silane coupling agent (manufactured by Shin-Etsu Chemical Co., Ltd., product name "KBM-403") were blended with 100 parts of the solid content of the acrylic polymer A2 solution to obtain adhesive PSA3.
[0111] [Production Example 6: Preparation of adhesive] (Preparation of Acrylic Polymer A3) A solution of acrylic polymer A3 having Mw of 2.7 million and Mw / Mn of 3.8 was prepared in the same manner as in Production Example 3, except that a monomer mixture containing 91 parts of butyl acrylate, 6 parts of N-acryloylmorpholine, 0.3 parts of 4-hydroxybutyl acrylate and 2.7 parts of acrylic acid was used.
[0112] (Preparation of Adhesive) 0.1 parts of trimethylolpropane / tolylene diisocyanate adduct (manufactured by Tosoh Corporation, product name "Coronate L"), 0.3 parts of peroxide crosslinking agent (manufactured by Nippon Oil & Fats Corporation, product name "Niper BMT"), and 0.2 parts of epoxy group-containing silane coupling agent (manufactured by Shin-Etsu Chemical Co., Ltd., product name "KBM-403") were mixed with 100 parts of the solid content of the acrylic polymer A3 solution to obtain adhesive PSA4.
[0113] [Production Example 7: Preparation of adhesive] (Preparation of Acrylic Polymer A4) A solution of acrylic polymer A4 having Mw of 2.2 million was prepared in the same manner as in Production Example 3, except that a monomer mixture containing 82.1 parts of butyl acrylate, 13 parts of benzyl acrylate, 0.1 parts of 4-hydroxybutyl acrylate and 4.8 parts of acrylic acid was used.
[0114] (Preparation of Adhesive) 0.5 parts of a polyether compound having a reactive silyl group (manufactured by Kaneka Corporation, product name "Silyl SAT10"), 0.45 parts of a trimethylolpropane / tolylene diisocyanate adduct (manufactured by Tosoh Corporation, product name "Coronate L"), and 0.1 parts of a peroxide crosslinking agent (benzoyl peroxide) were blended with 100 parts of the solid content of the acrylic polymer A4 solution to obtain adhesive PSA5.
[0115] [Production Example 8: Preparation of polarizing plate] (Preparation of polarizer) A long roll of polyvinyl alcohol (PVA) resin film (manufactured by Kuraray, product name "PE3000") with a thickness of 30 μm was uniaxially stretched in the longitudinal direction to 5.9 times its original size using a roll stretching machine while simultaneously undergoing swelling, dyeing, crosslinking, and washing processes, and finally a drying process to produce a polarizer with a thickness of 12 μm. Specifically, the film was stretched 2.2 times during the swelling treatment in pure water at 20°C. Next, the film was stretched 1.4 times during the dyeing treatment in an aqueous solution at 30°C in which the weight ratio of iodine to potassium iodide was 1:7, and the iodine concentration was adjusted so that the single transmittance of the resulting polarizer was 45.0%. Furthermore, a two-stage crosslinking treatment was adopted, and the film was stretched 1.2 times during the first stage crosslinking treatment in an aqueous solution at 40°C in which boric acid and potassium iodide were dissolved. The aqueous solution in the first stage crosslinking treatment had a boric acid content of 5.0% by weight and a potassium iodide content of 3.0% by weight. The film was stretched 1.6 times during the second stage crosslinking treatment in an aqueous solution at 65°C in which boric acid and potassium iodide were dissolved. The aqueous solution in the second stage crosslinking treatment had a boric acid content of 4.3% by weight and a potassium iodide content of 5.0% by weight. The cleaning treatment was performed with an aqueous potassium iodide solution at 20° C. The aqueous solution used for the cleaning treatment had a potassium iodide content of 2.6% by weight. Finally, the film was dried at 70° C. for 5 minutes to obtain a polarizer.
[0116] (Preparation of polarizing plate) A triacetyl cellulose film (thickness: 40 μm, manufactured by Konica Minolta, product name "KC4UYW") was attached to one side of the above polarizer via a polyvinyl alcohol adhesive to obtain a polarizing plate P1 having a protective layer / polarizer configuration.
[0117] [Production Example 9: Preparation of polarizing plate] (Preparation of polarizer) As a thermoplastic resin substrate, a long amorphous isophthalic copolymerized polyethylene terephthalate film (thickness: 100 μm) having a Tg of about 75° C. was used, and one side of the resin substrate was subjected to a corona treatment. A PVA aqueous solution (coating solution) was prepared by adding 13 parts by weight of potassium iodide to 100 parts by weight of a PVA-based resin made by mixing polyvinyl alcohol (polymerization degree 4200, saponification degree 99.2 mol%) and acetoacetyl-modified PVA (manufactured by Nippon Synthetic Chemical Industry Co., Ltd., product name "GOHSEFFIMER") in a ratio of 9:1, and dissolving the mixture in water. The above PVA aqueous solution was applied to the corona-treated surface of a resin substrate and dried at 60° C. to form a PVA-based resin layer with a thickness of 13 μm, thereby producing a laminate. The obtained laminate was uniaxially stretched 2.4 times in the machine direction (longitudinal direction) in an oven at 130° C. (auxiliary air stretching treatment). Next, the laminate was immersed in an insolubilizing bath (a boric acid aqueous solution obtained by mixing 4 parts by weight of boric acid with 100 parts by weight of water) at a liquid temperature of 40° C. for 30 seconds (insolubilizing treatment). Next, the film was immersed in a dye bath (an aqueous iodine solution obtained by mixing iodine and potassium iodide in a weight ratio of 1:7 with 100 parts by weight of water) at a liquid temperature of 30°C for 60 seconds while adjusting the concentration so that the single transmittance (Ts) of the finally obtained polarizer would be the desired value (dyeing treatment). Next, the piece was immersed in a crosslinking bath (a boric acid aqueous solution obtained by mixing 3 parts by weight of potassium iodide and 5 parts by weight of boric acid with respect to 100 parts by weight of water) at a liquid temperature of 40° C. for 30 seconds (crosslinking treatment). Thereafter, the laminate was immersed in an aqueous boric acid solution (boric acid concentration: 4% by weight, potassium iodide concentration: 5% by weight) at a liquid temperature of 70°C and uniaxially stretched in the longitudinal direction (longitudinal direction) between rolls with different peripheral speeds to a total stretch ratio of 5.5 times (underwater stretching treatment). Thereafter, the laminate was immersed in a cleaning bath (an aqueous solution obtained by mixing 4 parts by weight of potassium iodide with 100 parts by weight of water) at a liquid temperature of 20° C. (cleaning treatment). Thereafter, the film was dried in an oven maintained at about 90° C. while being brought into contact with a SUS heated roll whose surface temperature was maintained at about 75° C. (drying shrinkage treatment). In this manner, a polarizer having a thickness of about 5 μm was formed on the resin substrate, and a polarizing plate having a resin substrate / polarizer structure was obtained.
[0118] (Preparation of polarizing plate) A cycloolefin film (ZF-12, 23 μm, manufactured by Zeon Corporation) was attached as a protective layer to the surface of the obtained polarizer (the surface opposite to the resin substrate) via an ultraviolet-curable adhesive. Specifically, the curable adhesive was applied so that the total thickness was about 1.0 μm, and the layers were attached using a rolling machine. Thereafter, the adhesive was cured by irradiating it with UV light from the cycloolefin film side. Next, the resin substrate was peeled off to obtain a polarizing plate P2 having a cycloolefin film (protective layer) / polarizer configuration.
[0119] [Examples 1 to 5 and Comparative Examples 1 to 8] A polarizing plate, a retardation film (retardation layer), and an adhesive (first adhesive layer and second adhesive layer) were combined as shown in Table 1 to prepare a retardation layer and an adhesive layer-attached polarizing plate. Here, the polarizing plate and the retardation layer (retardation film) were attached so that the absorption axis of the polarizer and the slow axis of the retardation film formed an angle of 45°. The obtained retardation layer and the adhesive layer-attached polarizing plate were subjected to the evaluation of the above-mentioned color unevenness. The results are shown in Table 1 together with the adhesive slippage of the first adhesive layer, the shrinkage rate of the retardation layer, and the creep value of the second adhesive layer. In the "Size" column in Table 1, "M" means 77.4 mm x 162.3 mm size, and "T" means 159.5 mm x 244.5 mm size.
[0120] [Table 1]
[0121] [evaluation] As is clear from Table 1, by controlling the adhesive slippage amount of the first adhesive layer, the shrinkage rate of the retardation layer, and the creep value of the second adhesive layer in combination, it is possible to obtain a polarizing plate with a retardation layer and an adhesive layer that can realize an image display device in which color unevenness in a high-temperature environment is suppressed. [Industrial Applicability]
[0122] The retardation layer and pressure-sensitive adhesive layer-attached polarizing plate of the present invention can be suitably used in image displays (typically, liquid crystal displays and organic EL displays). [Explanation of symbols]
[0123] 10 Polarizing plate 11 Polarizer 12 First protective layer 13 Second layer of protection 20 First adhesive layer 30 Retardation layer 40 Second adhesive layer 100 Polarizing plate with retardation layer and adhesive layer
Claims
1. a polarizing plate including a polarizer, a retardation layer bonded to the polarizing plate via a first pressure-sensitive adhesive layer, and a second pressure-sensitive adhesive layer provided as an outermost layer on a side of the retardation layer opposite to the polarizing plate; the polarizer is made of a polyvinyl alcohol-based resin film containing iodine, the retardation layer is composed of a stretched resin film, satisfies the relationship Re(450)<Re(550), and has a shrinkage rate of 4% or less in the slow axis direction when heated at 80° C. to 125° C. for 180 minutes; The resin film contains a resin having positive refractive index anisotropy, the resin including at least one bonding group selected from the group consisting of a carbonate bond and an ester bond, and at least one structural unit selected from the group consisting of a structural unit represented by the following general formula (1) and a structural unit represented by the following general formula (2), and an acrylic resin: The adhesive slippage of the first pressure-sensitive adhesive layer after a heating test at 85° C. for 500 hours is 300 μm or more. Polarizing plate with retardation layer and adhesive layer: 【Chemistry 1】 【Chemistry 2】 In general formulae (1) and (2), R 1 to R 3 are each independently a direct bond or a substituted or unsubstituted alkylene group having 1 to 4 carbon atoms, R 4 to R 9 are each independently a hydrogen atom, a substituted or unsubstituted alkyl group having 1 to 10 carbon atoms, a substituted or unsubstituted aryl group having 4 to 10 carbon atoms, a substituted or unsubstituted acyl group having 1 to 10 carbon atoms, a substituted or unsubstituted alkoxy group having 1 to 10 carbon atoms, a substituted or unsubstituted aryloxy group having 1 to 10 carbon atoms, a substituted or unsubstituted amino group, a substituted or unsubstituted vinyl group having 1 to 10 carbon atoms, a substituted or unsubstituted ethynyl group having 1 to 10 carbon atoms, a sulfur atom having a substituent, a silicon atom having a substituent, a halogen atom, a nitro group, or a cyano group; provided that R 4 to R 9 may be the same or different from one another, and at least two adjacent groups among R 4 to R 9 may be bonded to each other to form a ring, Re(450) and Re(550) are in-plane retardations measured at 23° C. with light having wavelengths of 450 nm and 550 nm, respectively.
2. The retardation layer has an Re(550) of 100 nm to 200 nm, and the angle between the slow axis of the retardation layer and the absorption axis of the polarizer is 40° to 50° or 130° to 140°.
3. 3. The polarizing plate with a retardation layer and a pressure-sensitive adhesive layer according to claim 1, wherein the retardation layer has a thickness of 15 μm to 60 μm.
4. 4. The polarizing plate with a retardation layer and a pressure-sensitive adhesive layer according to claim 1, wherein the stretched film constituting the retardation layer is subjected to a heat treatment at a temperature of 105° C. or higher for 2 minutes or longer.
5. The retardation layer and the adhesive layer-attached polarizing plate according to any one of claims 1 to 4, further comprising another retardation layer between the retardation layer and the second adhesive layer, the refractive index characteristics of which are in the relationship of nz>nx=ny.
6. The retardation layer and the pressure-sensitive adhesive layer-attached polarizing plate according to any one of claims 1 to 5, wherein the content of the acrylic resin is 0.5% by mass to 2.0% by mass when the total amount of the resin in the resin film is 100% by mass, and the acrylic resin contains 70% by mass or more of a structural unit derived from methyl methacrylate when the total amount of the structural units constituting the acrylic resin is 100% by mass, and the weight average molecular weight Mw is 10,000 to 200,000.
7. An image display comprising the retardation layer according to claim 1 and a pressure-sensitive adhesive layer-attached polarizing plate.
Citation Information
Patent Citations
Optical retardation plate and manufacturing method thereof
JP1993249315A
Polycarbonate type biaxially oriented film and retardation film
JP2004082714A
Laminated optical film, elliptically polarizing plate and image display device
JP2008046147A
Adhesive retardation layer-stuck polarizing plate, optical film and image display device
JP2011013684A
Method for manufacturing retardation film and method for manufacturing circular polarization plate
JP2014194483A